Experimental measurements of saturated vapor pressure and gaseous pvT property for 2, 3, 3, 3-tetrafluoroprop-1-ene (HFO-1234yf). (November 2019) - Yin, Jianguo; Zhao, Guanjia; Ma, Suxia
Abstract: The saturated vapor pressures and gaseous pvT properties of 2, 3, 3, 3-tetrafluoroprop-1-ene (HFO-1234yf) were measured using a Burnett apparatus. 24 vapor pressure data points were obtained in temperature range from (253 to 367) K and with pressures from (0.15 to 3.34) MPa. The standard experimental uncertainties were estimated to be within 5 mK and 0.5 kPa for temperature and pressure, respectively. The vapor pressure data were correlated by a Wagner type equation with the average absolute deviation of 0.015%. A total of 172 gaseous pvT data were obtained in temperature range from (253 to 368) K, pressure range from (0.097 to 3.37) MPa and density range from (0.038 to 2.86) mol dm –3 . The relative uncertainty in density is better than 0.15%. The present data were correlated by a truncated virial equation of state with the average absolute deviation of 0.03% in density.